Controlling Uncertainty with Proactive Cyber Defense: A Clausewitzian Perspective - Sampsa Rauti (My University, 2025)
This study argues that the fundamental tenets Carl von Clausewitz presented about warfare in his influential book On War can be applied to defensive cyberwar. This will help in forming a new multidisciplinary perspective on the topic, which can benefit policy makers, political and military scientists and cyber security specialists alike. Moreover, by applying Clausewitz's principles of defensive warfare and his concepts of uncertainty and friction to cyberdefense, we outline a conceptual framework for resilient and proactive cyberdefense.
Security in Computing and Communications: 7th International Symposium, SSCC 2019, Trivandrum, India, December 18–21, 2019, Revised Selected Papers